MCPIP1 ribonuclease can bind and cleave AURKA mRNA in MYCN-amplified neuroblastoma cells. Issue 1 (2nd January 2021) - Nowak, Iwona; Boratyn, Elżbieta; Student, Sebastian; Bernhart, Stephan F.; Fallmann, Jörg; Durbas, Małgorzata; Stadler, Peter F.; Rokita, Hanna
ABSTRACT: The role of the inflammation-silencing ribonuclease, MCPIP1 (monocyte chemoattractant protein-induced protein 1), in neoplasia continuous to emerge. The ribonuclease can cleave not only inflammation-related transcripts but also some microRNAs (miRNAs) and viral RNAs. The suppressive effect of the protein has been hitherto suggested in breast cancer, clear cell renal cell carcinoma, osteosarcoma, and neuroblastoma. Our previous results have demonstrated a reduced levels of several oncogenes, as well as inhibited growth of neuroblastoma cells upon MCPIP1 overexpression. Here, we investigate the mechanisms underlying the suppression of MYCN proto-oncogene, bHLH transcription factor ( MYCN )-amplified neuroblastoma cells overexpressing the MCPIP1 protein. We showed that the levels of several transcripts involved in cell cycle progression decreased in BE(2)-C and KELLY cells overexpressing MCPIP1 in a ribonucleolytic activity-dependent manner. However, RNA immunoprecipitation indicated that only AURKA mRNA (encoding for Aurora A kinase) interacts with the ribonuclease. Furthermore, the application of a luciferase assay suggested MCPIP1-dependent destabilization of the transcript. Further analyses demonstrated that the entire conserved region of AURKA seems to be indispensable for the interaction with the MCPIP1 protein. Additionally, we examined the effect of the ribonuclease overexpression on the miRNA expression profile in MYCN -amplified neuroblastoma cells. However, no significant alterations were observed. Our data indicate a key role of the binding and cleavage of the AURKA transcript in an MCPIP1-dependent suppressive effect on neuroblastoma cells.